PENGARUH KONSUMSI SARI BUAH JAMBU BIJI TERHADAP KADAR HEMOGLOBIN IBU HAMIL DENGAN ANEMIA RINGAN DI PUSKESMAS MAJAULENG KAB.WAJO 2020 - Syamsuryanita Syamsuryanita; Nurul Ikawati (Sekolah Tinggi Pariwisata Mataram, 2022)
Iron deficiency anemia is one of the most common disorders, especially during pregnancy. Pregnant women are declared anemic if the hemoglobin (Hb) < 11 mg/L. Guava is a fruit that contains a lot of vitamin C. Guava can overcome anemia because in red guava fruit contains macro and micro nutrients, one of the micro nutrients is vitamin C which can accelerate the process of forming red blood cell hemoglobin. Helping the absorption of iron is vitamin C (ascorbic acid). The general purpose of this study was to determine the effect of consuming red guava juice on hemoglobin levels in pregnant women with mild anemia at the Majauleng Health Center, Wajo Regency 2020. The research method used in this study. is a Quasi Experiment method. The sampling technique in this study was purposive sampling, in this study the researcher used the Pretest-Posttest Control Group Design. Respondents in this study were 30 people. Giving red guava juice once a day with Fe tablets for 7 days. Before and after administration, Hb levels were measured using Easy Touch GChB. Data analysis was carried out first to test for normality because the conditions for using T Paired Test data must be normally distributed, and the results of the T Paired Test statistic test obtained p value = 0.000 (p <0.05). The results showed that there was an effect of red guava juice on changes in hemoglobin levels in first trimester pregnant women with value = 0,001< (0,05). It is hoped that this study can increase knowledge about the effect of consuming red guava juice on hemoglobin levels of pregnant women with anemia